Promosi dan Kualitas Produk terhadap Minat Beli Produk Coklat Desa Talang Pagar Agung Kecamatan Pajar Bulan Kabupaten Lahat - Indra Hartini; Iskandar Iskandar; Emila Sholiha (IPM2KPE, 2024)
This research aims to determine and analyze the influence of promotions, the influence of product quality, the influence of promotions and product quality in determining interest in buying chocolate products in Talang Pagar Agung Village. Secondary data shows that the percentage increase in chocolate business in Talang Pagar Agung Village in the past 3 years has increased, where in From 2021 to 2022, the development of Talang Pagar Agung Village Chocolate business will increase by 10%. In this research the researcher used a descriptive type of research with a quantitative approach which can basically be used from one of the existing methods. This research uses a quantitative approach because the research data obtained uses numbers and the analysis uses statistics. The results of the research, namely partial (individual) tests, show that product quality and promotion have a positive effect on consumer buying interest in chocolate in Talang Pagar Agung Village, Pajar Bulan District, Lahat Regency and simultaneously have a positive and significant effect on buying interest in chocolate businesses in Talang Pagar Agung Village. In conclusion, there is an influence of product quality and promotion on consumer buying interest. Managerial implications for chocolate producers to focus more on improving product quality and innovation, as well as packaging that is not only attractive but can also improve the shelf life of chocolate. Keywords: Promotion, Product Quality, Purchasing Decisions